The Relationship between Learning Styles and Creative Thinking and Problem-Solving Abilities of Students at SMK Negeri 1 Kisaran - Muhammad Razali; Cut Latifah Zahari (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
The aim of this study is to examine the impact of students’ learning styles visual, auditory, and kinesthetic on their creative thinking and problem-solving abilities. This research employed a quantitative approach with a comparative descriptive method. Data were collected through descriptive and inferential analysis. The study population consisted of 340 eleventh-grade students of SMK Negeri 1 Kisaran, from which 78 students were selected as samples using purposive sampling. Research instruments included a 39-item learning style questionnaire, 5 items measuring mathematical creative thinking skills, and 5 items assessing problem-solving skills. Data were analyzed using multivariate techniques with the MANOVA test. The findings indicate that learning styles significantly influence both creative thinking and problem-solving abilities, with a contribution of 57.1%. This result suggests that students’ visual, auditory, and kinesthetic learning styles play an important role in shaping their creative thinking and problem-solving skills.